The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1073/pnas.0401393101
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional termination by RNA polymerase I requires the small subunit Rpa12p

Abstract: We identify Rpa12p of RNA polymerase I (Pol I) as a termination factor. Combined analyses using transcription run-on, electron microscopy-visualized chromatin spreading and RT-PCR have been applied to the rRNA-encoding genes of Saccharomyces cerevisiae. These confirm that Pol I termination occurs close to the Reb1p-dependent terminator in wild-type strains. However, deletion mutants for the 3 end-processing enzyme Rnt1p or the Rpa12p subunit of Pol I both show Pol I transcription in the spacer. For ⌬rpa12, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
98
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 33 publications
16
98
1
Order By: Relevance
“…While C11 is implicated in RNAPIII reinitiation (see below), Rpb9 might regulate arrest of elongating RNAPII at pause sites (Awrey et al 1997). TRO analysis and electron microscopy (EM) visualization of Miller spreads demonstrated the involvement of Rpa12 in RNAPI termination (Prescott et al 2004;Kawauchi et al 2008). These experiments link transcription termination and processing of pre-rRNA.…”
Section: Coupling Of Rrna Processing and Terminationmentioning
confidence: 90%
See 2 more Smart Citations
“…While C11 is implicated in RNAPIII reinitiation (see below), Rpb9 might regulate arrest of elongating RNAPII at pause sites (Awrey et al 1997). TRO analysis and electron microscopy (EM) visualization of Miller spreads demonstrated the involvement of Rpa12 in RNAPI termination (Prescott et al 2004;Kawauchi et al 2008). These experiments link transcription termination and processing of pre-rRNA.…”
Section: Coupling Of Rrna Processing and Terminationmentioning
confidence: 90%
“…Inactivation of Rnt1 causes read-through at T1, indicating that, as with protein-coding genes, cotranscriptional cleavage is important for efficient termination Prescott et al 2004;Kawauchi et al 2008). Recently, Catala et al (2008) showed that Rnt1 interacts with two RNAPIspecific subunits, Rpa12 and Rpa34.…”
Section: Coupling Of Rrna Processing and Terminationmentioning
confidence: 99%
See 1 more Smart Citation
“…16). The composite active site of Pol I and III enables efficient proofreading 9,17 and termination 18,19 .…”
Section: Composite Active Centrementioning
confidence: 99%
“…Rpa190 was depleted in a tet:: regulated allele; Rpa12 encodes a nonessential subunit of Pol I involved in transcription termination and was directly obliterated in the genome of haploid yeast cells. Logarithmic yeast cultures were treated with 10% sarkosyl, which permeabilizes cell membranes and reversibly blocks elongating polymerases (Prescott et al 2004), incubated with [a 32 P]-UTP and transcription allowed to resume for the optimized labeling time of 5 min. Neosynthesized, radiolabeled transcripts were extracted, partially hydrolyzed, and used to probe slot-blots loaded with singlestranded DNA fragments complementary to the entire rDNA locus (Fig.…”
Section: Christmas Tree Visualization In Vivo By Ch-ipmentioning
confidence: 99%